2021
DOI: 10.3390/rs13030333
|View full text |Cite
|
Sign up to set email alerts
|

Explanation and Probabilistic Prediction of Hydrological Signatures with Statistical Boosting Algorithms

Abstract: Hydrological signatures, i.e., statistical features of streamflow time series, are used to characterize the hydrology of a region. A relevant problem is the prediction of hydrological signatures in ungauged regions using the attributes obtained from remote sensing measurements at ungauged and gauged regions together with estimated hydrological signatures from gauged regions. The relevant framework is formulated as a regression problem, where the attributes are the predictor variables and the hydrological signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
(100 reference statements)
2
7
0
Order By: Relevance
“…Category Climate Land/water use Physiography slowly through time compared to climate, we observed seasonal patterns in drying event type (Figure 3), and previous studies have shown that climate is the most important factor in predicting mean annual no flow occurrence (Hammond et al, 2021;Tyralis et al, 2021).…”
Section: Predictor Variablesupporting
confidence: 56%
See 2 more Smart Citations
“…Category Climate Land/water use Physiography slowly through time compared to climate, we observed seasonal patterns in drying event type (Figure 3), and previous studies have shown that climate is the most important factor in predicting mean annual no flow occurrence (Hammond et al, 2021;Tyralis et al, 2021).…”
Section: Predictor Variablesupporting
confidence: 56%
“…The dominant importance of land cover/use and physiography relative to climate is surprising, given that land cover/use and physiography change relatively PRICE ET AL. slowly through time compared to climate, observed seasonal patterns in drying event type (Figure 3), and previous studies have that climate is the most important factor in predicting mean annual no flow occurrence (Hammond et al, 2021;Tyralis et al, 2021).…”
Section: Dominant Watershed Properties and Climate Drivers Of Drying ...supporting
confidence: 56%
See 1 more Smart Citation
“…The quantile loss function can substitute the squared error function (or its equivalents) in hydrological models tailored to deliver forecasts; therefore, one can directly obtain quantile forecasts using a single model or post-process quantile simulation in the data assimilation procedure. Finally, similar methodological themes to those proposed in this work, including several ones for issuing point [90] and probabilistic [91] predictions of hydrological signatures, could be provided by exclusively using hydrological models instead of relying on data driven-ones. Other similar themes for improved quantile-based predictions are those combining multiple hydrological models and more [30].…”
Section: Discussionmentioning
confidence: 87%
“…More precisely, Tyralis, Papacharalampous, Langousis, et al. (2021) have compared boosting with linear models as base learners and boosting with a combination of linear models and stumps as base learners (Bühlmann & Hothorn, 2007; Hofner et al., 2014; Hothorn et al., 2020) in probabilistically predicting −in quantile regression settings− mean daily discharge, 5% flow quantile, 95% flow quantile, baseflow index, average duration of high‐flow events, frequency of high‐flow days, average duration of low flow events, frequency of low‐flow days, runoff ratio, streamflow precipitation elasticity, slope of the flow duration curve and mean half‐flow date in 667 catchments in the contiguous United States. They have found that the former boosting algorithm performs better than the latter in predicting signature quantiles at levels 2.5% and 97.5%, while the opposite holds for the prediction of the median.…”
Section: Introductionmentioning
confidence: 99%